2013
DOI: 10.1149/04512.0009ecst
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Extinction Process of Ionic Vacancy by the Cyclotron MHD Electrode

Abstract: From the lifetime measurement of ionic vacancy with a new type of electrode called cyclotron magnetohydrodynamic electrode (MHDE), two extinction processes of ionic vacancy were clarified; one is the decay to the initial state, and the other is the conversion to nanobubbles with the collision of the ionic vacancies. As a result, in copper electrodeposition, the formation time of the nanobubble was obtained as 0.072 s, whereas the intrinsic lifetime of the ionic vacancy without collision was determined as 8.6 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…8 In all cases, the collision between ionic vacancies decreased the lifetime down to 1/100th of the intrinsic value. As predicted by the preceding papers, 6,10,11 these results suggested that nanobubbles arise from the collision of ionic vacancies. However, nanobubbles are too small to observe, so that for the visualization of the bubble formation, some other process to yield much larger bubbles was required.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…8 In all cases, the collision between ionic vacancies decreased the lifetime down to 1/100th of the intrinsic value. As predicted by the preceding papers, 6,10,11 these results suggested that nanobubbles arise from the collision of ionic vacancies. However, nanobubbles are too small to observe, so that for the visualization of the bubble formation, some other process to yield much larger bubbles was required.…”
Section: Introductionsupporting
confidence: 73%
“…In cathodic reactions such as copper deposition, negatively charged ionic vacancies are created, yielding negatively charged nanobubbles surrounded by positively charged ionic clouds. Due to positively charged outer ionic clouds, 6,11 The first two authors contributed equally to this work. nanobubbles are once adsorbed on the negatively charged electrode in a cathodic polarization.…”
Section: Microbubble Formation By the Cyclotron Effect Of Vertical Mhmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Ionic vacancies flowing with the solution collide with ionic vacancies newly created on the electrode, transformed into nanobubbles. As a result, the intrinsic lifetime without collision is about 1.0 s, whereas the formation time of nanobubble in the case of perfect collision is about 10 ms.…”
Section: Theoreticalmentioning
confidence: 99%
“…Recently, the measurements of their partial molar volumes and lifetimes have revealed that ionic vacancies are created with electrode reactions. [1][2][3][4][5] At the same time, the nanobubble formation from supersaturated ionic vacancies has been theoretically clarified. 6,7 However, due to their sizes of about 0.1 nm and lifetimes of about 1 s, the direct observation of ionic vacancies is difficult.…”
Section: Introductionmentioning
confidence: 99%